1998
DOI: 10.2307/3284670
|View full text |Cite
|
Sign up to set email alerts
|

Meningoencephalitis Due to a Sarcocystis Neurona-like Protozoan in Pacific Harbor Seals (Phoca vitulina richardsi)

Abstract: Seven Pacific harbor seals with meningoencephalitis associated with Sarcocystis neurona-like protozoa are described. Six of the 7 seals were free-ranging and were found stranded over an 80-km stretch of central California coastline; the other was captive. All had marked to severe nonsuppurative meningoencephalitis, most severe in the cerebellar cortex. Immunohistochemistry for S. neurona antigens was positive on brain tissue in all cases, revealing numerous merozoites as well as developing and mature schizonts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
52
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 23 publications
4
52
0
Order By: Relevance
“…Because we did not evaluate muscle cysts using PCR we could not verify that cysts were the same species of Sarcocysts as those in the brain. Brain lesions were most severe in the cerebellum, similar to that reported in Pacific harbor seals (Phoca vitulina richardsi) (Lapointe et al, 1998). This case is also similar to other cases in seals (Lapointe et al, 1998) and turkeys (Teglas et al, 1998;Dubey et al, 2000), because sarcocysts were also observed in both striated muscle and myocardium.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Because we did not evaluate muscle cysts using PCR we could not verify that cysts were the same species of Sarcocysts as those in the brain. Brain lesions were most severe in the cerebellum, similar to that reported in Pacific harbor seals (Phoca vitulina richardsi) (Lapointe et al, 1998). This case is also similar to other cases in seals (Lapointe et al, 1998) and turkeys (Teglas et al, 1998;Dubey et al, 2000), because sarcocysts were also observed in both striated muscle and myocardium.…”
supporting
confidence: 82%
“…Brain lesions were most severe in the cerebellum, similar to that reported in Pacific harbor seals (Phoca vitulina richardsi) (Lapointe et al, 1998). This case is also similar to other cases in seals (Lapointe et al, 1998) and turkeys (Teglas et al, 1998;Dubey et al, 2000), because sarcocysts were also observed in both striated muscle and myocardium. Sarcocystis falcatula was ruled out in one of the turkeys without protozoal encephalitis because schizonts were not found in endothelial cells and the organism did not react to anti-S. falcatula antibody.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…12,14 The culture-confirmed S. neurona true-positive serum samples used in this analysis were highly consistent in their reactivity to those specific proteins. The results of this study also demonstrate that the Western blot S. neurona antibody test can be subject to false-positive results because of antibody cross-reactivity.…”
Section: Discussionmentioning
confidence: 78%
“…7 Recent work indicates that immunodominant proteins of approximately 29 and 17 kD are specific to S. neurona, which suggests a different criterion for a positive test than that reported previously. 12,14 The purposes of this study were to develop the most stringent criteria possible for a positive test result, to estimate the sensitivity and specificity of the EPM Western blot antibody assay, and to test the ability of bovine antibodies to S. cruzi to act as a blocking agent to prevent false-positive results in the Western blot test for S. neurona.…”
mentioning
confidence: 99%